The Effect of Song in Teaching English - Nurfajri Ningsih (ELTIES : English Language Teaching for EFL Learners, 2019)
This research aims at finding the effectiveness of using song in teaching English at Sulawesi flight college. The researcher applied pre-experimental method, with one group pretest and posttest design which employed speaking test to find out the students’ speaking performance in terms of accuracy. The sample consisted of 40 students used purposive sampling technique taken from the population of the second semester students of Sulawesi Flight. The result of the data analysis indicated that there was significant difference of student’ English achievement before and after being taught by using songs. It is proved by result of statistical analysis of the level significance 0.05 with degree of freedom (df) =  N-1 = 46-1 = 39 which indicated that( t- obs =  4.06 >  t –table =  (1.68 ). It can be said that there is a significant difference of achievement of the students after the treatment.